Enhancing sustainability in the cattle meat supply chain : a multicriteria sorting decision-making model and negotiation protocols - CAUSIL, Over Manuel Montes (2023)
This thesis focuses on the selection of sustainable meat packaging suppliers, as the sustainability of the supply chain significantly depends on inputs from this support network. Therefore, the main objective is to propose decision and multicriteria negotiation models that facilitate the classification and selection of suppliers, as well as the acquisition of packaging, with the aim of driving the strategic development of a sustainable supply chain in the cattle meat industry. The first proposed model serves as a guide for categorizing suppliers using the Value-Focused Thinking (VFT) approach and the multicriteria flexible and interactive trade-off (FITradeoff) method. This model aims to sort suppliers, suggesting improvements and advances in operations towards sustainable development. The second model, in addition to employing the FITradeoff procedure to select a single supplier, introduces an agent-based negotiation protocol. This protocol includes the evaluation of offers, concession magnitude, and counteroffer functions for both agents, allowing the automated exchange of offers between buyers and sellers. An innovation of this protocol is its ability to reward suppliers who implement sustainable strategies and demonstrate low complaint rates. The third model proposes a negotiation process based on the FITradeoff procedure, which differs from the previous model by significantly reducing the number of trading packages during the elicitation of scale constants. These models are useful for searching for long-term contract suppliers and registered suppliers. The models are applied to case studies conducted at a large company in the northern region of Colombia. Socially, this thesis contributes to the pursuit of fair wages and workers’ well-being. Ecologically, it stands out for its focus on the sustainability of the cattle meat supply chain through the implementation of strategic recommendations aligned with development goals. This thesis assists leaders and companies in choosing sustainable suppliers and provides suggestions for improving the performance of these suppliers in terms of sustainability. From a technological perspective, the proposition of an autonomous negotiating agent adds value to the e- commerce literature in the agribusiness sector, serving as a starting point for the development of electronic trading support systems and B2B e-commerce, resulting in the transition of agribusiness to the digital era (e-agribusiness). Additionally, it contributes to the reduction of management risks and microbiological contamination in the meat supply chain, thus minimizing public health problems.